Exploring access to social protection by persons with disabilities in Bangladesh - Mizanur Rahman; Md Shohel Rana; Md Mostafizur Rahman; Md Nuruzzaman Khan (PLoS ONE, 2025)
Background Social protection programs have played a significant role in ensuring that persons with disabilities (PWD) in low- and middle-income countries have access to basic livelihoods. However, there is a lack of research examining the extent of social protection program coverage for PWD and the factors influencing their inclusion. This study aimed to explore the extent of PWD’s inclusion in social protection programs in Bangladesh and the factors influencing their inclusion in these programs. Methods We analyzed data from the 2021 National Household Survey on Persons with Disabilities in Bangladesh. The outcome variable considered was PWD’s inclusion in social protection programs (yes, no) to receive support, as well as the timing of inclusion in the social protection program (non-inclusion (0), inclusion within 0–6 months of the survey (1), and inclusion more than 6 months before the survey (2)). Explanatory variables included factors at the individual, household, and community levels. A multilevel multinomial logistic regression model was used to explore the associations between the outcome variable and explanatory variables, with respondents categorized into two groups based on age (children (0 to <18) and adults and older (18–95 years)). Results Data from a total of 4,293 PWD were analyzed, with a mean age of 41.4 years; 59% of the respondents were male. Approximately 37.7% (95% CI, 36.0–39.6) of the total respondents reported inclusion in social protection programs within 0–6 months of the survey, rising to 47.4% (95% CI, 45.6–49.2) for support received more than 6 months before the survey. “Disability allowances (69.0%) were the most common type of social protection program that PWD reported being included in, followed by old age allowances (16.3%) and assistance through the VGD/VGF programs (6.8%). Among children aged <18 years, the likelihood of inclusion in social protection programs was higher for those with multiple disabilities. In contrast, for PWD aged 18 years and older, inclusion in social protection programs was lower among those with mental illness, hearing disabilities, and intellectual disabilities. The likelihood of inclusion in social protection programs was higher for older, unmarried, widowed, divorced, or separated PWD. Conversely, PWD from wealthier households and those residing in the Dhaka division had a lower likelihood of being included in social protection programs. Conclusion The findings of this study underscore the urgent need for more comprehensive and inclusive social protection policies and programs to support the well-being of PWD in Bangladesh. Since disability grants are the primary source of social protection for this group, it is crucial to expand coverage and increase the amount of financial support provided.